THE EFFECT OF WORK TRAINING AND CAREER DEVELOPMENT ON THE WORK PRODUCTIVITY OF PT ARISTA JAYA LESTARI'S EMPLOYEES - Yulius Jatmiko Nuryatno; Yosef Budiarso Martono (Jurnal Ekonomi, 2023)
PT Arista Jaya Lestari is an official dealer for the Wuling brand that carries out 3S (Sales, Service, Spareparts) business activities. Employee work productivity at PT Arista Jaya Lestari in 2021 is not optimal, this is shown from the sales target and the results of the employee Key Performance Index in 2021 have not been achieved. Therefore this study aims to determine the causes of decreased employee productivity at PT Arista Jaya Lestari and to find a relationship either partially or simultaneously between the effects of job training and career development on employee productivity using multiple linear regression analysis method. The population in this study were all employees of PT Arista Jaya Lestari with a total of 30 people, so the sampling technique in this study used a saturated sample technique with a total of 30 respondents. While the data analysis technique used is the instrument feasibility test, classical assumption test, multiple linear regression analysis, T test, F test, and the coefficient of determination. In this study, it was found that the results of the T-test, the job training variable had a significant effect on work productivity variables, and the career development variable also had a significant effect on work productivity variables. From the results of the F test, it was found that the variables of job training and career development simultaneously have a significant influence on work productivity variables.